KEBERADAAN PENGGUNAAN BAHASA INDONESIA PADA GENERASI MILENIAL - Nanda Saputra (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2020)
Indonesian as the official language of the country has been used as an oral and written communication tool in a variety of purposes, both formal and informal. Indonesian plays an important role in all aspects of life. The current situation is that the function of the Indonesian language has begun to be replaced or displaced by foreign languages ​​and there is behavior that tends to slip foreign terms, even though there is an equivalent in the Indonesian language, because of an attitude that believes that it will look modern, and educated and with the reason to facilitate communication in the millennial era. The symptoms of the above language phenomena are examined using sociolinguistics qualitatively. Data collection using a questionnaire containing 35 foreign vocabularies, to be answered equivalents in Indonesian form by respondents. Respondents in this study were MAS Unggul Nurur Rasyad Al-Aziziyah Tijue students and Tarbiyah Al-Hilal Sigli High School students, who were sampled from the population using purposive and random sampling techniques. The data that has been collected is then analyzed using the matching method with a translational langue determination tool. The results obtained, MAS Unggul Nurur Rasyad Al-Aziziyah Tijue based on a questionnaire were all students mastering the equivalent in Indonesian from 9 vocabularies, then vocabulary only partially mastered by 3 students and for vocabularies that were not mastered by the Indonesian equivalent by all 23 students . While out of 35 foreign language vocabularies, all students of Tarbiyah Al-Hilal Sigli High School semester VI of the Madrasah Ibtidaiyah Teacher Education Study Program, did not know the Indonesian equivalent of 16 vocabularies, then 6 vocabularies were mastered by only a small proportion of students and all students knew the equivalent in Indonesian 13 vocabulary words.